Endoscopic findings and outcomes of gastric mucosal changes relating to potassium‐competitive acid blocker and proton pump inhibitor therapy - Satoshi Shinozaki; Hiroyuki Osawa; Yoshimasa Miura; Hiroaki Nomoto; Hirotsugu Sakamoto; Yoshikazu Hayashi; Tomonori Yano; Edward J. Despott; Hironori Yamamoto (DEN Open)
Abstract Gastric mucosal changes associated with long‐term potassium‐competitive acid blocker and proton pump inhibitor (PPI) therapy may raise concern. In contrast to that for PPIs, the evidence concerning the safety of long‐term potassium‐competitive acid blocker use is scant. Vonoprazan (VPZ) is a representative potassium‐competitive acid blocker released in Japan in 2015. In order to shed some comparative light regarding the outcomes of gastric mucosal lesions associated with a long‐term acid blockade, we have reviewed six representative gastric mucosal lesions: fundic gland polyps, gastric hyperplastic polyps, multiple white and flat elevated lesions, cobblestone‐like gastric mucosal changes, gastric black spots, and stardust gastric mucosal changes. For these mucosal lesions, we have evaluated the association with the type of acid blockade, patient gender, Helicobacter pylori infection status, the degree of gastric atrophy, and serum gastrin levels. There is no concrete evidence to support a significant relationship between VPZ/PPI use and the development of neuroendocrine tumors. Current data also shows that the risk of gastric mucosal changes is similar for long‐term VPZ and PPI use. Serum hypergastrinemia is not correlated with the development of some gastric mucosal lesions. Therefore, serum gastrin level is unhelpful for risk estimation and for decision‐making relating to the cessation of these drugs in routine clinical practice. Given the confounding potential neoplastic risk relating to H. pylori infection, this should be eradicated before VPZ/PPI therapy is commenced. The evidence to date does not support the cessation of clinically appropriate VPZ/PPI therapy solely because of the presence of these associated gastric mucosal lesions.